Fictional Practice from Antiquity to Today - Otto, Bernd-Christian (Fictional Practice: Magic, Narration, and the Power of Imagination, 2021)
The purpose of this concluding chapter is to summarise and synthesise the findings of the entire volume, to weave red threads through the material discussed therein, and to discuss three different types of relationships between fiction and practice that manifested in the history of Western learned magic. Section 1 discusses cases in which fiction has informed practice. Section 2 reverses the perspective and assembles cases in which practice has informed fiction. Section 3 focuses on cases in which the boundaries between fiction and practice are blurred, concluding with unique types of ‘fictional practice’ that seem to have emerged as a culmination of this phenomenon. Assuming that the case studies assembled in the volume are representative of the history of Western learned magic at large, the chapter finally discusses various arguments for a historical trajectory that led to a heightened degree of fiction-practice entanglements from the nineteenth century onwards.<br